Finite set predictive torque control based on sub-divided voltage vectors of PMSM with deadbeat control and discrete space vector modulation - Alsofyani, Ibrahim Mohd; Kim, Seok Min; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2019)
The conventional finite set-predictive torque control (FS-PTC) of permanent magnet synchronous motor (PMSM) is known for its easy implementation, fast torque performance, and capability to include the constraints and nonlinearities. However, the most notable problems in the classical FS-PTC are the long calculation time and large current and torque ripples. This paper presents a simple FS-PTC with discrete space vector modulation (DSVM) and a deadbeat control (DBC) for PMSM drives. In this method, the DSVM is utilized to increase the number of virtual voltage vectors without the need for complex lookup tables or initialization requirement. The proposed DBC strategy is designed aiming to reduce the computation burden while widening the selected zones of candidate voltage vectors in the prediction steps. The proposed FCS-PTC of PMSM has also other advantages; such as reduction of torque and flux ripples, constant switching frequency owing to the use of DSVM, robustness against parameter variations due to the increase of candidate voltage vectors considered in the cost function, and easy implementation. The effectiveness of the proposed control strategy is verified by simulation results using PSIM software package.
Keywords: Calculation time; Computation burden; Constant switching frequency; Control strategies; Deadbeat control; Discrete space vector modulation; Permanent Magnet Synchronous Motor; Predictive torque controls; Deadbeat control; Discrete space vector modulation; Predictive torque control